HLA-class II genes association with multiple sclerosis: An immunogenetic prediction among multiple sclerosis Jordanian patients - Sawsan I. Khdair; Lubna Al-Khareisha; Osama H. Abusara; Alaa M. Hammad; Alaa Khudair (PLoS ONE, 2025)
Multiple sclerosis (MS) is an inflammatory autoimmune disease affecting the central nervous system (CNS). The pathogenesis of MS is characterized by neuronal axonal degeneration and demyelination. Among the genes that raises MS risk are the HLA-class II genes. The goals of this study were to investigate the role of the HLA-DRB1 and HLA-DQB1 genes (for the first time) in Jordanian MS patients and their association with MS disease. The association of these genes with other clinical features, such as optic neuritis, sensory impairment, and brainstem symptoms in MS patients was investigated as well using PCR-SSP techniques. Our findings indicated an association between HLA-DRB1 * 03:01 (Pc =  0.01) and HLA-DRB1 * 04:01 (Pc =  0.004) alleles with Jordanian MS patients. In addition, a significant linkage between HLA-DRB1 * 15:01 and HLA-DQB1 * 06:01 alleles (Pc ≤  0.001 and Pc =  0.012, respectively) were presented among Jordanian MS patients with optic neuritis compared to Jordanian MS patients without optic neuritis. Moreover, HLA-DQB1 * 05:01 and HLA-DQB1 * 06:02 alleles (Pc ≤  0.001 and Pc =  0.006, respectively) was found to be related with sensory impairment in MS patients. Additionally, HLA-DRB1 * 07:01 allele indicates a positive correlation in MS patients with brainstem symptoms (Pc <  0.001). Moreover, our results indicated that there is no association on the HLA-DRB1 ~ HLA-DQB1 haplotype level and MS disease. Knowing the genes that are linked to MS, they may facilitate MS diagnosis, prevention, and treatment at earlier stage. Also, these results may serve in the development of more potent therapeutic regimens for MS and its related complications, such as optic neuritis, sensory impairment, and brainstem symptoms.